2007
DOI: 10.1103/physrevlett.98.227801
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Viscoelastic Effects in Surface Capillary Waves of Molten Polymer Films

Abstract: The surface dynamics of supported ultrathin polystyrene films with thickness comparable to the radius of gyration were investigated by surface sensitive x-ray photon correlation spectroscopy. We show for the first time that the conventional model of capillary waves on a viscous liquid has to be modified to include the effects of a shear modulus in order to explain both static and dynamic scattering data from ultrathin molten polymer films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 24 publications
7
94
2
Order By: Relevance
“…In a reversal of the above observations, as the molecular mass of matrix PS chains further increases, the AuPS particles become more concentrated in the trenches (K > 1), whereas the matrix polymer chains segregate into the mesas due to more significant entropic penalty under confinement. It should be noted, however, that, in the case of ultrathin trench confinement (i.e., h 2 ≈ 2R g,PS ), only partial depletion of matrix PS chains was observed, as the mobility of polymer chains was significantly suppressed beyond practical equilibration times (27).…”
Section: Resultsmentioning
confidence: 99%
“…In a reversal of the above observations, as the molecular mass of matrix PS chains further increases, the AuPS particles become more concentrated in the trenches (K > 1), whereas the matrix polymer chains segregate into the mesas due to more significant entropic penalty under confinement. It should be noted, however, that, in the case of ultrathin trench confinement (i.e., h 2 ≈ 2R g,PS ), only partial depletion of matrix PS chains was observed, as the mobility of polymer chains was significantly suppressed beyond practical equilibration times (27).…”
Section: Resultsmentioning
confidence: 99%
“…A couple of the remarkable studies will be reviewed here. The overdamped capillary waves of polystyrene films are observed by Kim et al 60) and Jiang et al, 61,62) and they discussed the relation between the mobility of the polymer chains and the thickness of the film. Madsen et al observed the dispersion relation of the capillary waves on liquid surface near the transition point from oscillating to overdamped behavior.…”
Section: X-ray Photon Correlation Spectroscopymentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10][11] At third-generation synchrotrons it is nowadays possible to produce intense x-ray beam with a high degree of coherence. The scattered intensity distribution of such an x-ray beam coming from a rough surface provides a speckle pattern due to destructive and constructive interference.…”
Section: Introductionmentioning
confidence: 99%